Hey, could someone please solve this (go through each step if possible):
=(a/b-c/b)*(a-b/2(a/b-c/b))
The answer is apparently, (a^2/2b)-(c^2/2b), but I cant work it out
Thanks
That answer is correct; better shown as: (a^2 - c^2) / (2b)
Your expression is somewhat ambiguous (even if correctly shown); this is clearer:
(a/b - c/b) * [a - b(a/b - c/b) / 2]
Try this way:
x = (a/b - c/b) ; so expression becomes:
x * [(a - bx) / 2]
Continue...then substitute back in...OK?
Ah yes that does make it simpler.
But I think where I'm having trouble is simplifying after performing certain steps
For example (working within the second term), (a/b - c/b) = [(ab - cb) / b^2] = [(a - c )/ b], correct?
Then multiplying this by b = [(ba - bc)/b]?
Get the b terms together:
2b - ab = a
Factor:
b(2 - a) = a
Isolate b:
b = a / (2 - a)
Do some learning on your own:
Introduction to Algebra